Teleoncology: The Youngest Pillar of Oncology - Puneet Pareek; Jeewan Ram Vishnoi; Sri Harsha Kombathula; Rakesh Kumar Vyas; Sanjeev Misra (JCO Global Oncology, 2020)
The core pillars of multimodal care of patients with cancer are surgical, radiation, and medical oncology. The global pandemic of coronavirus disease 2019 (COVID-19) has suddenly resurrected a new pillar in oncology care: teleoncology. With oncologists reaching out to patients through telemedicine, it is possible to evaluate and fulfill patients’ needs; triage patients for elective procedures; screen them for influenza-like illness; provide them with guidance for hospital visits, if needed; and bridge oral medications and treatments when a hospital visit is not desirable because of any high risk-benefit ratio. Teleoncology can bring great reassurance to patients at times when reaching an oncology center is challenging, and more so in resource-constrained countries. Evidence-based treatment protocols, dispensable by teleoncology, already exist for many sites of cancer and they can provide a bridge to treatment when patients are unable to reach cancer centers for their standard treatment. The young pillar of teleoncology is going to remain much longer than COVID-19.